Arrhythmogenic effects of hypoglycemia in children and adolescents with type 1 diabetes mellitus - Dmitriy Nikitich Laptev; Galina Vladimirovna Ryabykina (Сахарный диабет, 2013)
Aim. To determine the effects of hypoglycemia on the duration of QT interval, heart rate variability (HRV) and frequency of arrhythmic events, as well as to closer investigate the factors associated with the development of various heart rhythm disorders in children and adolescents with type 1 diabetes mellitus (T1DM). Materials and methods.  The study included 150 children and adolescents with T1DM at the age of 6?18 years. All participants underwent Holter monitoring and continuous glucose monitoring (CGM) for 24 hours. QTc and HRV parameters (SDNN, RMSSD, SVVR) were calculated automatically. Data was averaged for 5?-interval and juxtaposed with CGM. Patients identified with hypoglycemic events (blood glucose